IMPORTANT PROFESSIONAL QUALITIES OF A VOLLEYBALL COACH ARE FOREIGN PSYCHOLOGISTS AS AN OBJECT OF STUDY - Inoyat ugli, Ibodov Azizbek (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2022)
When we study the research of psychologists from near and far abroad, we see that the teacher has made a valuable scientific note on the basics of professionally important quality techniques and the importance of socio-cultural, national-territorial and pedagogical education in this process.